Reduced erythrocyte susceptibility and increased host clearance of young parasites slows Plasmodium growth in a murine model of severe malaria - Khoury, David S. (Sci Rep, 2015)
The best correlate of malaria severity in human Plasmodium falciparum (Pf) infection is the total parasite load. Pf-infected humans could control parasite loads by two mechanisms, either decreasing parasite multiplication, or increasing parasite clearance. However, few studies have directly measured these two mechanisms in vivo. Here, we have directly quantified host clearance of parasites during Plasmodium infection in mice. We transferred labelled red blood cells (RBCs) from Plasmodium infected donors into uninfected and infected recipients, and tracked the fate of donor parasites by frequent blood sampling. We then applied age-based mathematical models to characterise parasite clearance in the recipient mice. Our analyses revealed an increased clearance of parasites in infected animals, particularly parasites of a younger developmental stage. However, the major decrease in parasite multiplication in infected mice was not mediated by increased clearance alone, but was accompanied by a significant reduction in the susceptibility of RBCs to parasitisation.